2020
DOI: 10.1016/j.stemcr.2020.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of Skin Precursor-Derived Schwann Cells Yields Better Locomotor Outcomes and Reduces Bladder Pathology in Rats with Chronic Spinal Cord Injury

Abstract: Summary Cell transplantation for spinal cord injury (SCI) has largely been studied in sub-acute settings within 1–2 weeks of injury. In contrast, here we transplanted skin-derived precursors differentiated into Schwann cells (SKP-SCs) into the contused rat spinal cord 8 weeks post-injury (wpi). Twenty-one weeks later (29 wpi), SKP-SCs were found to have survived transplantation, integrated with host tissue, and mitigated the formation of a dense glial scar. Furthermore, transplanted SKP-SCs filled m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 45 publications
2
23
0
Order By: Relevance
“…Moreover, the survival and recovery of damaged motoneurons might be attributed to the Akt/ mTOR/p70S6K signaling pathway activation mediated by SKP-SC-EVs. In agreement with these findings, the latest observation reported that SKP-SCs can yield better locomotor outcomes, and mitigate pathological thickening of the bladder wall in chronic SCI, the transplanted SKP-SCs reduced the formation of glial scarring, and greatly strengthened the presence of endogenous SCs, myelinating thousands of sprouting/spared host axons in and around the injury site (26).…”
Section: Discussionsupporting
confidence: 76%
“…Moreover, the survival and recovery of damaged motoneurons might be attributed to the Akt/ mTOR/p70S6K signaling pathway activation mediated by SKP-SC-EVs. In agreement with these findings, the latest observation reported that SKP-SCs can yield better locomotor outcomes, and mitigate pathological thickening of the bladder wall in chronic SCI, the transplanted SKP-SCs reduced the formation of glial scarring, and greatly strengthened the presence of endogenous SCs, myelinating thousands of sprouting/spared host axons in and around the injury site (26).…”
Section: Discussionsupporting
confidence: 76%
“…Apart from Sox10 and Egr2 , overexpression of other TFs expressed in repair Schwann cells, as described above (e.g., Sox2, Jun, Pax3, Egr1 , Olig1 ), may prove beneficial in improving reprogramming efficiencies. In the future, Schwann cells generated via direct differentiation or cellular reprogramming could be used in a stand-alone fashion for transplantation or supplemented in nerve conduits to aid nerve remyelination (Biernaskie et al, 2007 ; Mozafari et al, 2015 ; Sparling et al, 2015 ; Assinck et al, 2020 ). Schwann cells derived from rodent SKPs were demonstrated to successfully repair and remyelinate axons in the injured/diseased CNS as well (Biernaskie et al, 2007 ; Mozafari et al, 2015 ; Sparling et al, 2015 ; Assinck et al, 2020 ).…”
Section: Cellular Reprogramming For Peripheral Nerve Repairmentioning
confidence: 99%
“…Subsequent analysis reveals the survival of transplanted SCLCs for 5 months, their integration into host tissue, neural protection, axonal regeneration, and myelination. Further, the functional analysis reveals improved locomotion after 8 weeks of SCLCs transplantation [ 186 ].…”
Section: Origin and Therapeutic Effects Of Schwann Cell-like Cellsmentioning
confidence: 99%